Castor oil induces laxation and uterus contraction via ricinoleic acid activating prostaglandin EP3 receptors - Tunaru, Sorin; Offermanns, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Castor oil is one of the oldest drugs. When given orally, it has a laxative effect and induces labor in pregnant females. The effects of castor oil are mediated by ricinoleic acid, a hydroxylated fatty acid released from castor oil by intestinal lipases. Despite the wide-spread use of castor oil in conventional and folk medicine, the molecular mechanism by which ricinoleic acid acts remains unknown. Here we show that the EP3 prostanoid receptor is specifically activated by ricinoleic acid and that it mediates the pharmacological effects of castor oil. In mice lacking EP3 receptors, the laxative effect and the uterus contraction induced via ricinoleic acid are absent. Although a conditional deletion of the EP3 receptor gene in intestinal epithelial cells did not affect castor oil-induced diarrhea, mice lacking EP3 receptors only in smooth-muscle cells were unresponsive to this drug. Thus, the castor oil metabolite ricinoleic acid activates intestinal and uterine smooth-muscle cells via EP3 prostanoid receptors. These findings identify the cellular and molecular mechanism underlying the pharmacological effects of castor oil and indicate a role of the EP3 receptor as a target to induce laxative effects.
Gesehen am 07.11.2018